The Influence of Dividend Policy, Earnings Volatility and Leverage On Volatility of Jakarta Islamic Index (JII) Stock Prices - Sagala, Melia Br; H. Jamal; Wediawati, Besse; Musnaini (PT. Global World Scientific, 2024)
Stock price volatility is the movement up or down of stock prices. This study aims to determine the effect of dividend policy, earnings volatility and leverage on stock price volatility. This research was conducted on company shares in the Jakarta Islamic index. The sampling method used was purposive sampling and obtained a sample of 8 companies based on the criteria. The data analysis technique uses multiple linear regression. Data were obtained from financial reports, dividend distribution reports, and other literature.Based on the test results, it was found that dividend policy, earnings volatility, and leverage simultaneously have a significant effect on stock price volatility. Partially leverage has a significant effect on stock price volatility and dividend policy, earnings volatility has no significant effect on stock price volatility. The adjusted R Square value shows a value of 22.8% while the remaining 77.2% is influenced by other variables not included in this research model.